Psoas hitch procedure in 166 adult patients: The largest cohort study before the laparoscopic era. Issue 5 (6th April 2021) - Groen, V. H.; Lock, M. T. W. T.; de Angst, I. B.; Verhagen, P. C. M. S.; Horenblas, S.; Dik, P.; Bosch, J. L. H. R.
Abstract: Objectives: To present the short‐term and long‐term outcomes of the psoas hitch procedure in a large cohort with long‐term follow‐up. Patients and methods: A multicenter, retrospective cohort study was conducted. Patients were included if they had undergone an open psoas hitch procedure with ureteral reimplantation for different types of distal ureteral pathology between 1993 and 2017. Clinical failure was defined as radiologically‐proven obstruction of the ureteroneocystostomy and/or post‐operative complaints requiring additional surgery. Pre‐operative demographic data and post‐operative radiological imaging were collected. Complications were categorized as peri‐operative, acute (<30 days), and long‐term complications. Results: A total of 166 patients had undergone a psoas hitch procedure, with a median follow‐up of 15 months (IQR 6‐45). Indications for the procedure included intra‐operative injury of the ureter during gynecological, urological or general surgery, transitional cell carcinoma of the distal ureter, fistulae, (radiation) fibrosis, and trauma. There was no significant difference in pre‐ and post‐operative estimated glomerular filtration rate. Post‐operative complications included urinary leakage, recurrent urinary tract symptoms, recurrent malignancy, and kidney failure. Postoperative imaging was available in 143 patients. Failure of the psoas hitch procedure was seen in 8% (11/143) of the patients. In 55% (6/11) of these patients, radiation fibrosis was the indication for the psoas hitch procedure. Conclusion: This study provides greater insight into the long‐term complications of the open psoas hitch procedure in adults. The psoas hitch procedure can be considered a safe procedure for restoring the continuity of the ureter for different types of ureteral pathologies in adult patients. However, patients with a history of radiation therapy causing retroperitoneal fibrosis might be more prone to failure after the procedure.